PENGARUH DISIPLIN KERJA, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT. RAJAWALI CITRAMASS MOJOKERTO - Irwansyah, Ferri; -, Sukaris (Jurnal Manajemen, 2022)
This study aims to determine the effect of work discipline, reward, and punishment on employee performance at PT. Rajawali Citramass Mojokerto. This research is a quantitative research. The research instrument used in this study was a Likert scale questionnaire. The population used in this study were all employees of PT. Rajawali Citramass. The sample in this research was 45 employees. The sampling technique used in this study is the probability sampling technique. Data collection techniques are questionnaires, observation, interviews, and literature studies. The analytical method used is multiple linear analysis. The results showed that the work discipline variable partially had no significant effect on employee performance variables. The reward variable partially has a significant effect on employee performance variables. Punishment variable partially has no significant effect on employee performance variables. The variables of work discipline , reward and punishment simultaneously affect employee performance